Synthesis of Seven Membered Oxacycles: Recent Developments and New Approaches. Issue 43 (21st August 2020) - Sinka, Victoria; Martín, Víctor S.; Cruz, Daniel A.; Padrón, Juan I.
Abstract : This minireview focuses on recent advances in the synthesis of seven‐membered ring oxacycles, whether saturated, unsaturated, fused or isolated. We cover a remarkable variety of strategies and methods developed during the past two decades, based mainly on cyclizations, ring‐closing metathesis, conjugate additions, and ring expansions. The cyclizations can be generated directly or triggered through an oxocarbenium ion, carbocation or iminium‐type species. Also discussed are ring‐closing metatheses and conjugate additions, in which the precursor has the functionalities and correct stereochemistry of the final seven‐membered ring oxacycle. Finally, examples of ring expansions are described, predominantly involving cyclopropanes and epoxides. These cases include reactions governed by the intermediate species and others, where the precursor holds the stereochemical information for the final oxacycle. Abstract : This minireview cover the recent advances and methodologies, developed during the past two decades, in the synthesis of seven‐membered ring oxacycles. A wide range of methods have been developed to gain access to these oxacycles (saturated and unsaturated). These strategies are based on cyclizations (oxocarbenium ion, carbocation or iminium‐type species), ring‐closing metathesis, conjugate additions, and ring expansions (cyclopropanes and epoxides).